Review of the Stemonosudis rothschildi species complex, with descriptions of two new species from the Indo-west Pacific Ocean (Aulopiformes: Paralepididae) - Ho, Hsuan-Ching; Russell, Barry; Graham, Ken; Psomadakis, Peter N. (Zootaxa, 2019)
Three barracudina species are recognized in the Stemonosudis rothschildi species complex, which includes Stemonosudis rothschildi Richards, 1967, and two new species described herein. Stemonosudis multifasciatus sp. nov. is described based on five specimens collected off northwestern Australia and Myanmar, Eastern Indian Ocean. It is characterized by having 16 brownish blotches on dorsum (10 before dorsal-fin origin); 49–51 caudal vertebrae; 93‒95 total vertebrae; dorsal-fin origin relatively forward in position, distance between origins of pelvic and dorsal fins 52.3‒63.0% of distance between origins of pelvic and anal fins; and combination of body proportions. Stemonosudis retrodorsalis sp. nov. is described based on 15 specimens collected from off the Philippines, Indonesia and northwestern Australia. It is characterized by having dorsal-fin origin at about vertical through anal-fin origin, insertion of anal fin relatively forward, preanal length 71.5‒79.5% SL; 6 blotches on dorsum before DFO and 4 on abdominal ridge before VFO and unique combination of body proportions. A redescription of S. rothschildi, based on specimens collected from off Dongsha (Pratas) Islands, Australia and West Indies, is also included.